Microstrip Antenna Array Design for Unmanned Aerial Vehicles Detection Radar - Mendes Ruiz, P.; Begaud, X.; Magne, F.; Leder, E.; Khy, A. (Advanced electromagnetics, 2023)
This work presents the design and realization of four linear arrays of microstrip rectangular patch antennas. This linear array is one of the elements of a passive radar using signals from 4G base stations for UAV detection. The arrays have been validated and operate from 2.62 GHz to 2.69 GHz, with a HPBW of 82° in H-plane and a maximal gain going from 11.1 dB to 12.2 dB in the required bandwidth, with a cosecant squared pattern in the E-plane.